1992
DOI: 10.1080/02640419208729903
|View full text |Cite
|
Sign up to set email alerts
|

Physiological aspects of competitive cross‐country skiing

Abstract: The physiological demands of cross-country skiing require competitive skiers to have high maximal oxygen uptakes and anaerobic thresholds. Anaerobic capacity has a relatively less important role, but may be of greater importance today with the faster race velocities resulting from the new skiing techniques of ski skating. Although use of the ski skating techniques results in faster race velocities than the classical techniques, it has been found that under some conditions the double-pole technique is more econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 83 publications
2
27
0
1
Order By: Relevance
“…The order effect in the current study limits the confidence in the current findings relating to the performance outcome. There may be multiple reasons for the apparent order effect, including improving treadmill roller skiing technique, improving pacing strategies with increasing familiarization to the 30‐km TT course (Swart et al., ), and rapid physiological adaption to the exercise stimulus (Hoffman & Clifford, ; Jeukendrup, , ). While the extensive familiarization strategy applied in the current study was designed to prevent improvements in treadmill roller‐skiing technique throughout the trials, the possibility of this occurring cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The order effect in the current study limits the confidence in the current findings relating to the performance outcome. There may be multiple reasons for the apparent order effect, including improving treadmill roller skiing technique, improving pacing strategies with increasing familiarization to the 30‐km TT course (Swart et al., ), and rapid physiological adaption to the exercise stimulus (Hoffman & Clifford, ; Jeukendrup, , ). While the extensive familiarization strategy applied in the current study was designed to prevent improvements in treadmill roller‐skiing technique throughout the trials, the possibility of this occurring cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Female endurance athletes have a lower skeletal muscle mass (36) and a higher body fat (26) compared to male endurance athletes. A higher percentage of slow twitch muscle fibres and higher anaerobic threshold and low percentage of body fat have been observed in elite cross-country skiers (12,20,38).…”
Section: Best Performance Earlier In Life For Womenmentioning
confidence: 96%
“…This study has some limitations since anthropometric and physiological characteristics (39) as well as training aspects (23, 43) of these more than 66,000 finishers are not known. Furthermore, environmental conditions (47) and race equipment (20) might considerably influence race outcome. 'Vasaloppet' is a race performed in a relatively flat terrain, which implies the increased use of the upper-body dominant technique of double poling; thus, the present findings should not be generalized to races with large elevations.…”
Section: Limitations Strength and Practical Applicationsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] In standing skiers, DP is typically used under fast conditions or on moderate downhills, where a glide phase would occur after poling 7 because DP is more economical on flat terrain compared with other techniques. [11][12][13] Hoffman and Clifford 11 concluded that the DP technique was significantly more economical than skating or kick DP, as demonstrated by a 12% lower oxygen consumption in trained CC skiers, and they further supported these findings by demonstrating significantly lower oxygen consumption compared with the diagonal stride technique (26% lower) in elite CC skiers.…”
Section: Introductionmentioning
confidence: 99%